The Religion of White Rage Religious Fervor, White Workers and the Myth of Black Racial Progress - Finley, Stephen C.; Gray, Biko Mandela; Martin, Lori Latrice (Edinburgh University Press, 2020)
This book sheds light on the phenomenon of white rage, and maps out the uneasy relationship between white anxiety, religious fervour, American identity and perceived black racial progress.